Correction to: Histochemical Changes Liver and Kidney of Mice Exposed to Mercury and Recovery with Nanogold. Molekul, (2016) 11(1), 80-91. - - Editors (Universitas Jenderal Soedirman, 2017)
Corrigendum to:In Abstract typed as: